Cyclic hematopoiesis in a mixed-breed dog: case report and brief review. (November 2022) - Lee, Gary K. C.; Barbosa, Courtney; Andersen, Gitte; Ramirez, Christina J.; Kornya, Matthew; Abrams-Ogg, Anthony; Morrison, Katherine; Diamantino, Gabriella; Wood, R. Darren; Beeler-Marfisi, Janet; Ampuero, Fernanda; Tatiersky, Laetitia; et al.
An 8-wk-old, male, mixed-breed puppy was adopted from a rescue organization. From the time of adoption, the puppy suffered episodes of illness affecting various organ systems, which resolved with supportive therapy but relapsed once medical therapy was discontinued. Review of the hematologic data revealed cyclic fluctuations in circulating blood cells. Cyclicity was most prominent in neutrophils, with recurrent severe neutropenia. Neutropenic episodes lasted 5–6 d, with regular cycles of 11–14 d between nadir neutrophil counts. Genetic testing determined that the patient was homozygous mutant for the frameshift mutation in the adaptor protein complex 3 β-subunit ( AP3B1 ) gene, originally identified in gray collies with cyclic hematopoiesis (CH). Pedigree information was not available, but the patient's features were phenotypically distinct from those of collies. We describe here a case of the AP3B1 mutation in a mixed-breed dog that did not resemble a collie, undescribed previously, to our knowledge. Our findings indicate that the AP3B1 mutation and CH are present within the general canine population and are not restricted to collies.